Physical activity prevents blood pressure increases in individuals under treatment for knee osteoarthritis - Ciolac, Emmanuel G. [UNESP]; Rodrigues da Silva, Jose M. [UNESP]; Rezende, Marcia U. de (Lippincott Williams & Wilkins, 2018)
The aim of this study was to assess the role of physical activity in blood pressure (BP) in individuals with knee osteoarthritis. We compared 136 participants under treatment for primary knee osteoarthritis (age=67.6 +/- 9.6 years) allocated to the sedentary-sedentary, active-sedentary, sedentary-active, and active-active groups depending on their levels of daily physical activity before and after follow-up. Their BP, BMI, and endurance performance (6-min walking test) were compared during 12 months of follow-up. The sedentary-sedentary group had increased systolic BP (11 +/- 3mmHg), and the active-sedentary group had increased systolic (12 +/- 4mmHg) and diastolic BP (5 +/- 1mmHg) during follow-up. By contrast, the sedentary-active group maintained systolic BP and showed reduced diastolic BP (5 +/- 2mmHg), and the active-active group maintained both systolic and diastolic BP. Positive effects on BP were accompanied by improvements in endurance performance and BMI in the sedentary-active group (endurance performance=8.5 +/- 2.7%; BMI=9.3 +/- 3.6%) and the active-active group (endurance performance=2.9 +/- 0.9%; BMI=3.8 +/- 2.0%), which did not occur in the sedentary-sedentary and active-sedentary groups. These results suggest a positive role of high levels of daily living physical activity in the prevention/management of hypertension in individuals with knee osteoarthritis.
Keywords: hypertension; knee osteoarthritis; physical activity; prevention